2022
DOI: 10.21315/mjms2022.29.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Association between Socioeconomic Status and Vision Screening Outcomes among Preschool Children in Klang Valley, Malaysia: A Cross-Sectional Study

Abstract: Background: Vision screening programmes’ outcomes are routinely used to report the prevalence of vision anomalies in children. However, the association between vision screening outcomes and the children’s socioeconomic status remains underexplored. This cross-sectional study determined the association between socioeconomic and birth status with vision screening outcomes in a sample of children in Klang Valley. Methods: Total 411 children (mean age: 5.49 ± 0.47 years old) attending preschools were selected vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In TVPS-4, visual form constancy is measured by asking the participants to match two similar images, one of which could be bigger, smaller, or rotated. An earlier study on Malaysian preschoolers reported that Malay children were more likely to fail vision screening, and non-Malay children (including those of Chinese ethnicity) were likelier to have better visual acuity and stereopsis [ 16 ]. Both tasks involved object recognition and visual matching, which could be related to Malay children’s relatively lower visual form constancy performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In TVPS-4, visual form constancy is measured by asking the participants to match two similar images, one of which could be bigger, smaller, or rotated. An earlier study on Malaysian preschoolers reported that Malay children were more likely to fail vision screening, and non-Malay children (including those of Chinese ethnicity) were likelier to have better visual acuity and stereopsis [ 16 ]. Both tasks involved object recognition and visual matching, which could be related to Malay children’s relatively lower visual form constancy performance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, children from higher socioeconomic backgrounds typically outperform those from middle and low socioeconomic backgrounds [ 14 ]. A recent study reported that preschoolers from low-income families had lower than average visual–motor integration performance [ 15 ] and were likelier to fail visual screening tests [ 16 ] than those from higher-income families. Thus, young children’s visual perceptual abilities must be correctly measured, as they are crucial to their functional task performance [ 17 ] and, consequently, their school readiness.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for children from low-income families, these include the exacerbation of consumption of unhealthy diets [ 54 ] that is associated with lower academic performance [ 55 , 56 ]. Children from low-income families are also more likely to fail vision screening, indicating the presence of associated uncorrected refractive error and blurred vision [ 57 ]. Previous studies have shown that blurred vision, especially at near range, negatively impacts VMI performance in young children [ 58 ], reading and visual information processing during sustained near work [ 59 ], and academic performance [ 60 ].…”
Section: Discussionmentioning
confidence: 99%